Predictors of relapse in patients with Crohn's disease in remission after 1 year of biological therapy. Issue 2 (26th November 2012) - Molnár, T.; Lakatos, P. L.; Farkas, K.; Nagy, F.; Szepes, Z.; Miheller, P.; Horváth, G.; Papp, M.; Palatka, K.; Nyári, T.; Bálint, A.; Lőrinczy, K.; et al.
Summary Background Some of the most important questions relating to the use of biological therapy in inflammatory bowel diseases concern the duration of maintenance therapy. Aim To assess the disease course and frequency of relapse of Crohn's disease (CD) following discontinuation of biological therapy, and to determine predictive factors for relapse. Methods One hundred twenty‐one CD patients who had achieved clinical remission following 1 year of biological therapy and for whom biological therapy was then discontinued participated in this prospective observational study. Eighty‐seven CD patients had received infliximab and 34 adalimumab. The definition of relapse was an increase of >100 points in CDAI to at least a CDAI of 150 points. Results Biological therapy was restarted within 1 year of treatment cessation in 45% of patients. Logistic regression analysis revealed that previous biological therapy (P = 0.011) and dose intensification during the 1‐year course of biological therapy (P = 0.024) were associated with the need for and the time to the restarting of biological therapy. Smoking was observed to have an effect that was not statistically significant (P = 0.053). Conclusions Biological therapy was restarted a median of 6 months after discontinuation in almost half of Crohn's disease patients in who had been in clinical remission following 1 year of biological therapy. These results suggest that, in the event of the presence of certain predictive factors, biological therapy should probably be continued for more than 1 year by most patients.